The megalithic builders : new data on old bones from Megalitho do Facho (Figueira da Foz, Portugal) - Silva, Ana Maria (2020)
Between the end of the 19th and beginning of the 20th centuries, António dos Santos Rocha excavated several prehistoric megalithic monuments in the region of Figueira da Foz (Portugal). Some of them revealed human bones, albeit very disturbed and fragmented, which ended up forgotten in the Municipal Museum of Santos Rocha (Figueira da Foz), as did the individuals to which they belonged. Here, I revisit the human bone collection preserved from Megalitho do Facho to access demographic and morphological data; physiological stress indicators; pathologies and injuries that these individuals suffered, thus revealing insights on the lives of those who were deposited in this dolmen. The majority of this collection is composed of unburned bones and a small subsample of burned ones. Both were radiocarbon dated to the Chalcolithic period (first half of the 3rd millennium BC). The analysis confirmed that non-adult and adult individuals of both sexes were deposited in this dolmen. These individuals were affected by biomechanical stress since early in life and display mild signs of physiological stress associated with remodelled lesions, suggestive of a relatively good health status. These data are discussed in the context of other coeval sites.